Citizens’ preferences for policies to conserve agricultural genetic resources - Pouta, Eija; Tienhaara, Annika; Ahtiainen, Heini (European Association of Agricultural Economists (EAAE), 2014)
To evaluate conservation policies of agricultural genetic resources (AgGR), information on the use and non-use values of plant varieties and animal breeds, as well as on the preferences for in situ and ex situ conservation are needed. Here we present the results of a choice experiment of AgGR conservation programs in Finland. The findings indicate that citizens’ have high interest in the conservation of native breeds and varieties, but also that there is heterogeneity in preferences between citizens. Five groups can be identified: one implying lexicographic preferences, two with reasoned choices, one indicating ambivalence and one with status quo preferences.
Keywords: Maatalous - yleistä, maatalousekonomia,maatalousneuvonta, maaseudun kehittäminen; native breeds; native varieties; choice experiment; preference heterogeneity